University Entrepreneurship: Strategies for Developing and Diversifying Ventures to Support Higher Education Funding - Zahruddin Zahruddin; Sita Ratnaningsih (Dinamika Ilmu, 2026)
This study aims to uncover efforts to develop entrepreneurship in higher education after the Government, through the Ministry of Research, Technology, and Higher Education (Kemeristekdikti), issued a law that generally regulates the organization, management, and funding of higher education. Universities with legal entity status (PTN BH) face challenges related to limited government funding support amidst rising educational operational costs to maintain the quality of education and graduates. This research was conducted at the University of Indonesia. The research method used was descriptive-qualitative, with a case study. Data collection used observation techniques, in-depth interviews, and documentation, with the researcher acting as the main research instrument. Data analysis was carried out through the following stages: data collection, data condensation, data presentation, and conclusions. The results of the study indicate that entrepreneurship development through business creation begins with the change in the institution's status from a work unit (satker) to a legal entity with broader autonomy. Business development includes academic businesses, commercial businesses, and supporting businesses. Each business has its own purpose. Academic businesses aim to utilize the academic expertise of university members, commercial businesses aim to support university funding and improve and develop university resources, while supporting businesses aim to support academic activities and the welfare of the university community